Edukasi Teknik Pernapasan dalam (Deep Breathing) untuk Mengurangi Stres Menstruasi pada Siswi SMPN 2 Rambutan Kabupaten Banyuasin - Tri Sartika; Ayu Devita Citra Dewi (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Menstrual stress is a common reproductive health problem among adolescent girls, which can interfere with learning activities, concentration, and overall quality of life. This community service activity aimed to improve the ability of female students to manage menstrual stress through education and practice of deep breathing techniques at SMPN 2 Rambutan, Banyuasin Regency. The activity used a one-group pretest–posttest pre-experimental design involving 30 female students who had experienced menstruation. Health education was delivered through interactive lectures, discussions, and practical demonstrations of deep breathing techniques, while evaluation was conducted using pre-test and post-test questionnaires on menstrual stress levels. The results showed a reduction in menstrual stress, with most participants shifting from moderate stress before education to mild stress after the intervention. These findings indicate that deep breathing techniques are effective in helping students independently manage menstrual stress. Therefore, health education combined with practical deep breathing exercises is recommended to be implemented continuously in schools as a promotive and preventive strategy for adolescent reproductive health.